Try this option:
the rule: if f(-x)=f(x), then the function f(x) is even, if f(-x)=-f(x) then the function is odd.
1. f(x)=-5x⁴-2;
if to substitute x→(-x), then f(-x)=-5*(-x)⁴-2; ⇔ f(-x)=-5x⁴-2, in other words f(x)=f(-x), it means that this function is even.
2. f(x)=x³+2x.
if to substitute x→(-x), then f(-x)=(-x)³+2*(-x); ⇔ f(-x)=-(x³+2x), in other words f(-x)=-f(x), it means that this function is odd.
Answer:
11+2i=9
Step-by-step explanation:
Answer:
6/10 i think
Step-by-step explanation:
625 divided by 15 is 41.6 so i'd be 40+1+6/10
Answer:
9/5 (K-273.15) + 32=F
Step-by-step explanation:
K=5 /9(F−32)+273.15
Subtract 273.15 from each side
K-273.15=5/9(F−32)+273.15-273.15
K-273.15=5/9(F−32)
Multiply by 9/5 on each side
9/5 (K-273.15)= 9/5 *5/9(F−32)
9/5 (K-273.15)=(F−32)
Add 32 to each side
9/5 (K-273.15) + 32=F−32 +32
9/5 (K-273.15) + 32=F